Expressiveness as a Dominant Feature of the Idiostyle of Pavlo Zagrebelnyi (on the basis of the works “Kavtaklizma” and “Stovpo-tvorinnia”) - Кохан, Юрій Іванович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
Consideration is given to expressiveness as a feature of the idiostyle of Pavlo Zagrebelnyi. The language techniques of creation of expression in the satirical novels “Kavtaklizma” and “Stovpo-tvorinnia” are examined. The author’s typical techniques used for creation of language expression by means of split-level language units are defined and analyzed.